2022
DOI: 10.1038/s41598-022-21823-y
|View full text |Cite
|
Sign up to set email alerts
|

Excessive dietary linoleic acid promotes plasma accumulation of pronociceptive fatty acyl lipid mediators

Abstract: Various fatty acyl lipid mediators are derived from dietary polyunsaturated fatty acids (PUFAs) and modulate nociception. The modern diet is rich in linoleic acid, which is associated with nociceptive hypersensitivities and may present a risk factor for developing pain conditions. Although recommendations about fatty acid intake exist for some diseases (e.g. cardiovascular disease), the role of dietary fatty acids in promoting pain disorders is not completely understood. To determine how dietary linoleic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Chronically elevated levels of AA can contribute to a state of chronic inflammation and have been associated with autoimmunity [ 55 ]. This has led to some popular debate regarding the influence of LA intake on AA levels, with some recent papers suggesting that an excessive LA intake can lead to the accumulation of AA-derived pronociceptive lipid mediators and a reduction in antinociceptive lipid mediators obtained from omega-3 fatty acids [ 56 , 57 ]. However, a systematic review found that LA intake was not associated with tissue concentrations of AA in human beings [ 58 ].…”
Section: Pathophysiological Mechanism Of Elevated La Levelsmentioning
confidence: 99%
“…Chronically elevated levels of AA can contribute to a state of chronic inflammation and have been associated with autoimmunity [ 55 ]. This has led to some popular debate regarding the influence of LA intake on AA levels, with some recent papers suggesting that an excessive LA intake can lead to the accumulation of AA-derived pronociceptive lipid mediators and a reduction in antinociceptive lipid mediators obtained from omega-3 fatty acids [ 56 , 57 ]. However, a systematic review found that LA intake was not associated with tissue concentrations of AA in human beings [ 58 ].…”
Section: Pathophysiological Mechanism Of Elevated La Levelsmentioning
confidence: 99%